CagA+ H. pylori filtrate induces cytokine IL-8 secretion by esophageal squamous carcinoma EC 109 cells via a p38 pathway - Guan Xiao Ying; L I Wen Sheng; Zhang Li Xia; Wang Hong Tao (Wolters Kluwer Medknow Publications, 2014)
Background: The relationship between Helicobacter pylori (Hp) infection and the risk of esophageal squamous cell carcinoma is unclear. Aim: The purpose was to investigate the effects of CagA+ Hp on esophageal squamous carcinoma Ec 109 cells in vitro and explore the molecular mechanisms underlying these effects. Materials and Methods: Ec 109 cells were treated with CagA+ Hp filtrate at a concentration of 1.0 mg/mL or 50 μg/mL in vitro, proliferation and apoptosis of Ec 109 cells were assayed, the secretion of IL-8 was measured by ELISA, and the levels of Src homology-2 domain-containing phosphatase (SHP-2) mRNAs was assayed by RT-PCR.. Furthermore, after pretreatment of Ec109 cells with the specific p38 mitogen-activated protein kinase (MAPK) inhibitor SB203580, the p38 pathway was detected. Results: CagA+ Hp filtrate enhanced both the proliferation and apoptosis of Ec 109 cells. In addition, cytokine IL-8 release was significantly increased, and the expression of SHP-2 mRNA declined sharply in the CagA+ Hp group. Furthermore, after pretreatment of Ec109 cells with the specific p38 MAPK inhibitor SB203580, Ec109 cells proliferation and IL-8 secretion were inhibited. Conclusions: Our results suggest that CagA+ Hp filtrates could induce proliferation and the secretion of IL-8 by Ec109 cells in vitro. IL-8 secretion was induced through the activation of the p38 MAPK signal pathway.